Preliminary economics for green ammonia synthesis via lithium mediated pathway. (4th April 2021) - Gomez, Jamie R.; Garzon, Fernando
Summary: High energy density liquid fuel, ammonia, faces increasing interest globally as a carbon‐free energy carrier that can be transported over long distances for decentralized and remote distribution. The dominant ammonia production method, Haber‐Bosch, is both energy and carbon intensive to overcome the slow kinetics of the ammonia synthesis reaction from nitrogen and hydrogen. An early techno‐economic model for lithium mediated electrochemical ammonia synthesis at mild process conditions using feed rates of 27 metric ton/day for lithium hydroxide, 127 metric ton/day for cryogenic nitrogen and 264 metric ton/day electrolysis grade water is presented. Further analysis was carried out to analyze the energy consumption and reduction per metric ton of ammonia in comparison to electrochemical ammonia using H+ conductive membrane and small‐scale Haber‐Bosch technology. Electrochemical ammonia synthesis using lithium‐ion conductive membrane coupled with nitrogen generation by cryogenic distillation was found to be a sustainable pathway. The ammonia production cost via lithium mediated pathway was estimated to be less than $700 per metric ton and was found to be comparable with costs using traditional Haber Bosch. The environmental impact of electrochemical ammonia using the alkali group 1 metal, lithium, was also assessed from cradle to product. Abstract : Low temperature lithium mediated electrochemical ammonia production using a cheap renewable electricity source exhibited similar economics as traditional Haber‐ Bosch. About a quarter less energy is consumed for the lithium‐based approach to ammonia production, suggesting a more competitive path to proton conducting systems